EVALUASI MODEL PENGERINGAN LAPISAN TIPIS JAGUNG (ZEA MAYS L) VARIETAS BIMA 18 DAN BIMA 16 - Poerwanty, Henny; Nildayanti, Nildayanti; Syatrawati, Syatrawati (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2024)
Drying is one of the most important things done in the post-harvest process. This research aims to determine the pattern of decreasing water content in hybrid corn varieties Bima 18 and Bima 16, as well as to obtain an appropriate mathematical model of thin layer drying. The method used is the trial fitting method with the Newton Model, Henderson and Pabis Model, Page Model, Midilli et al. Model, and the two-term exponential model. Drying of thin layers of hybrid corn Bima 18 and Bima 16 at temperatures of 40°C and 50°C showed an exponential pattern. The most suitable corn drying model for the Bima 18 and Bima 16 varieties and at temperatures of 40°C and 50°C is the Midilli et.al model and the two-term exponential model. Awm2-4e of 40°C is R2=0.9986 and the Bima 16 variety has R2=0.9961, while the Two Term Exponential model value for the Bima 18 variety at a temperature of 50° is R2 = 0.9988 and the Bima 16 variety has R2 = 0.9938.